Investigation of curing kinetics analysis and their effects on properties of epoxy: polystyrene blending (Baghdad Science Journal, 2024)
The effect of curing conditions, such as temperature, concentration of toughening material, such as polystyrene, on epoxy resin cure kinetics was studied, along with the effects of curing parameters, such as degree of cure (α) and glass transition temperature (Tg), mechanical properties, thermal properties (TGA), and morphology of epoxy and its blends. Tg, degree of cure, and thermal stability measures were calculated from a DSC chart, mechanical properties (tensile strength, elastic modulus, and elongation at break) were measured using a universal tensile machine, the curing process was the same for all samples with varying temperatures, and the morphology of fracture surface Clearfield was examined using SEM. The samples were prepared by mixing two sets of (resin/hardener)+polystyrene (PS) (0, 2.5 % Wt., 5% Wt., and 7.5% Wt.) by mechanical stirring. The first set was cured at room temperature, while the second set was cured at 80 °C. The chart is drawn with the content of PS, as the degree of value is converging. The value of Tg in the first set decreased in comparison with neat epoxy resin along with increasing polystyrene content, then increased at 5% Wt., 7.5% Wt. PS at room temperature while deceased with 80 °C. The mechanical properties decreased at both room temperature and 80 °C. The thermal stability in the first stage showed good stability with increasing temperature the degradation become faster until reach charring of the sample. SEM was used to examine the broken surface's morphology after PS cure at room temperature reduced.